Clinical evaluation of a polymerase chain reaction assay to detect Aspergillus species in bronchoalveolar lavage samples of neutropenic patients - Buchheidt, Dieter; Baust, Corinna; Skladny, Heyko; Baldus, Michael; Bräuninger, Susanne; Hehlmann, Rüdiger (British journal of haematology, 2002)
Summary. The increasing incidence of invasive aspergillosis, a life-threatening infection in immunocompromised patients, emphasizes the need to improve the currently limited diagnostic tools. Using a recently developed two-step polymerase chain reaction (PCR) assay to detect 10 fg of Aspergillus DNA, corresponding to 1-5 colony-forming units (CFU)/ml of spiked samples in vitro, we prospectively examined 197 bronchoalveolar lavage (BAL) samples from 176 subjects, including 141 neutropenic, febrile patients with lung infiltrates, at risk for invasive fungal disease. Underlying diseases of these patients were haematological malignancies; 93 patients suffered from acute leukaemias. Thirty-one of these immunocompromised patients (17·6%) were PCR positive, correlating with positive BAL culture, positive histology from lung surgery or from autopsy, positive computerized tomography scans or positive galactomannan enzyme-linked immunosorbent assay. Six patients (4·3%) of this group had positive PCR results without any correlation to clinical or other diagnostic data, probably owing to contamination of the samples by ubiquitous Aspergillus spores. The samples of two patients (1·4%) with a subsequent histologically proven mould infection were PCR negative. All 102 immunocompromised patients (72·3%) with a negative PCR showed no evidence of invasive fungal disease. From 35 patients without immunodeficiency, four (11·4%) showed positive results, without evidence of invasive or non-invasive pulmonary aspergillosis. In this haematological population, the sensitivity and specificity values of the test reached 93·9% and 94·4%, the positive predictive value 83·8%, the negative predictive value 98·1%. Our data support the considerable clinical value of this PCR assay for confirming and improving diagnosis of pulmonary aspergillosis in high-risk patients.
Gesehen am 17.05.2022